2017
DOI: 10.12737/article_59acaae9dad902.64338769
|View full text |Cite
|
Sign up to set email alerts
|

Trpm8 Gene Polymorphism and Smoking as the Factors of Severe Bronchial Obstruction in Patients With Asthma

Abstract: The aim of the study was to determine the role of rs11562975 polymorphism of TRPM8 gene and tobacco smoking in the formation of severe bronchial obstruction in asthma patients. According to this aim, 416 patients with varying severity of asthma were examined. The study design included standard spirometry, genotyping of rs11562975 TRPM8 gene polymorphism and evaluation of the status and duration of smoking. The study revealed the detrimental effect of smoking on the respiratory function in patients with a pack/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
2
1
0
3
Order By: Relevance
“…Correlation analysis showed that the degree of bronchial obstruction had a tendency to aggravation with the increase in the number of the T alleles. In addition, we replicated the effect of TRPM8 rs11562975 on lung function that was previously found in smoking asthma patients [33]. There are no previous studies that estimated the influence of TRPM8 and TRPA1 polymorphisms on lung function in COPD, so the identified associations are now reported for the first time.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Correlation analysis showed that the degree of bronchial obstruction had a tendency to aggravation with the increase in the number of the T alleles. In addition, we replicated the effect of TRPM8 rs11562975 on lung function that was previously found in smoking asthma patients [33]. There are no previous studies that estimated the influence of TRPM8 and TRPA1 polymorphisms on lung function in COPD, so the identified associations are now reported for the first time.…”
Section: Discussionsupporting
confidence: 82%
“…Carriers of the heterozygous genotype had the highest bronchodilator response (ΔFEV1 17.3 (12.1-27.9)%) when compared with the AA (12.1 (4.2-22.8)%, p = 0.02) or GG genotypes (2.7 (0.1-23.0)%, p = 0.04), whereas the difference between the homozygous genotypes was not significant. Despite that there were no obvious and strong associations with lung function for TRPM8 rs11562975 in COPD, we took a closer look at this polymorphism since its influence on FEV1 and FEV1/FVC was established in our previous studies in asthma patients, including those with smoking history > 10 pack-years [28,33]. In accordance with these data, we noticed that in COPD patients the C allele of TRPM8 rs11562975 had a trend to association with lower post-bronchodilator FEV1/FVC (GG-48.9 (41.4-55.8)%, GC-45.7 (38.1-50.9)%, CC-35.2 (32.7-37.7)%).…”
Section: Associations Of Trpm8 and Trpa1 Polymorphisms With The Airwamentioning
confidence: 99%
“…При этом, носители GC и CC составляли, соответственно, 18,1 и 1,8% у больных БА с ИТ<80%, но в два раза реже встречались среди пациентов с ИТ≥80% (9,2 и 0,8%, соответственно). Различия были значимы при сравнении в доминантной (ОШ 2,2 [1,49], p=0,03) и аддитивной моделях (p=0,03), а также при анализе частот аллелей (p=0,02).…”
Section: результаты исследования и их обсуждениеunclassified
“…Прежде нами была выявлена ассоциация полиморфизма rs11562975 гена холодовых рецепторов TRPM8 с повышенной частотой формирования тяжелой бронхиальной обструкции (ОФВ 1 <60%) у больных БА с индексом курильщика 10 пачка-лет и более [1]. В настоящем исследовании целью было изучить независимое влияние данного полиморфизма на функцию легких и обратимость бронхиальной обструкции среди больных БА легкой и средней степени тяжести.…”
unclassified
See 1 more Smart Citation